2007
DOI: 10.1021/cg060615t
|View full text |Cite
|
Sign up to set email alerts
|

Cuprous Oxide Nanowires Prepared by an Additive-Free Polyol Process

Abstract: The polyol method was employed for the first time to synthesize cuprous oxide nanowires using only a precursor of Cu(II) acetate monohydrate and diethylene glycol (DEG). With careful control of the reaction temperature (190 °C), the precursor concentration (0.01−0.1 mol/L), and the reaction time (6 h), we prepared Cu2O nanowires with a diameter of approximately 20 nm and a length up to 5 μm. The nanowires were characterized by SEM, TEM, XRD, and IR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 31 publications
(72 reference statements)
4
50
0
Order By: Relevance
“…Apparently, there were two extra peaks (at 1647 cm −1 and 629 cm −1 ) in the FTIR spectrum of the as-synthesized Cu 2 (OH) 3 reported was between 620 and 634 cm −1 . The slight shift in peak position could be the effect of reduction in particle size [30][31][32][33][34].…”
Section: Characterization Of Cu 2 (Oh) 3 Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, there were two extra peaks (at 1647 cm −1 and 629 cm −1 ) in the FTIR spectrum of the as-synthesized Cu 2 (OH) 3 reported was between 620 and 634 cm −1 . The slight shift in peak position could be the effect of reduction in particle size [30][31][32][33][34].…”
Section: Characterization Of Cu 2 (Oh) 3 Nomentioning
confidence: 99%
“…Cu 2 O is an important p-type semiconductor which can be used as a photocatalyst to degrade organic pollutions under visible light irradiation, but the research of Cu 2 O as a Fenton-like catalyst without light irradiation has not been reported [29,32]. In copper-based Fenton-like heterogeneous system, such as CuO, Cu-pillared clays, and Cu-exchange zeolites as catalysts, Cu(II) is considered as the active species in general.…”
Section: Characterization Of Cu 2 (Oh) 3 Nomentioning
confidence: 99%
“…In the polyol process, derivatives of glycol serve as solvent, stabilizer and reducing agent; and also control the growth of nanostructures. Orel et al synthesized Cu 2 O coneshaped bundles made by nanowires in the polyol diethylene glycol (DEG) [30], but uniform Cu 2 O nanoparticles in the polyols ethylene glycol (EG) and tetraethylene glycol (TEG) [31]. Chainlike metal-glycolate complexes obtained by refluxing metal precursors in EG were transformed to the metal-oxide wire-like morphology after additional heating at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the morphology of the CuO particles has also been the matter of concern in other advanced applications such as glucose sensing [15], catalysis [16], etc. Hence, scientists have focused on the development of methods and operational strategies for controlling particle morphologies of CuO which include polyol [17], hydrothermal [18], sol-gel [19], thermal oxidation [20], etc. These efforts led to the production of CuO powders, composed of nanoflowers [16], nanowires [20], and nanoribbons [21].…”
Section: Introductionmentioning
confidence: 99%